2014
DOI: 10.1186/s13010-014-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of animal research: a survey of pediatric health care workers

Abstract: IntroductionPediatric health care workers (HCW) often perform, promote, and advocate use of public funds for animal research (AR). We aim to determine whether HCW consider common arguments (and counterarguments) in support (or not) of AR convincing.DesignAfter development and validation, an e-mail survey was sent to all pediatricians and pediatric intensive care unit nurses and respiratory therapists (RTs) affiliated with a Canadian University. We presented questions about demographics, support for AR, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Previous surveys have generally asked only whether people support AR for human benefit, and have not asked people to evaluate their reasons for supporting (or not) AR [ 16 – 20 ]. When we presented common arguments and counterarguments to a small sample of pediatric health care workers at our children’s hospital, we found that most were not convinced of the moral permissibility of AR [ 21 ]. Here, we survey a large sample of the public, medical students, academic pediatricians, and scientists to determine their considered opinions regarding the moral permissibility of AR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys have generally asked only whether people support AR for human benefit, and have not asked people to evaluate their reasons for supporting (or not) AR [ 16 – 20 ]. When we presented common arguments and counterarguments to a small sample of pediatric health care workers at our children’s hospital, we found that most were not convinced of the moral permissibility of AR [ 21 ]. Here, we survey a large sample of the public, medical students, academic pediatricians, and scientists to determine their considered opinions regarding the moral permissibility of AR.…”
Section: Introductionmentioning
confidence: 99%
“…However, several projects discussed a broad range of animals, like rabbits, bovines, pigs, snakes, goats, lizard, hamsters, embryonated eggs and other [1][2][3][4]. It has been figured that over 100 million animals are practiced in the world for research each year [11][12][13][14][15]. The present study from Questionnaire in 2004 to 2017, the researchers, and review scientific documents.…”
Section: Statisticmentioning
confidence: 99%
“…The development and reporting of the questionnaire followed published recommendations [11][12][13][14][15]. The framework section pronounced "In this survey, animals intends rat in the first level without avoiding other mammals, such as mice, dogs, cats, and others.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations